GALLIUM NITRIDE POWER ELECTRONICS FOR AEROSPACE - MODELLING AND SIMULATION: GALLIUM NITRIDE POWER ELECTRONICS FOR AEROSPACE - MODELLING AND SIMULATION - Gramatikov, Pavlin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Modelling and simulation of power GaN HEMT transistors and GaN devices are presented. Comparison and parameters for different GaN products are shown.